Prediking in ’n multimedia-kultuur. Homiletiese beginsels vir ’n interaktiewe kommunikasiepraxis - Smit, Guillaume (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
This article investigates the art of preaching culture from the perspective of the developing digital culture engulfing contemporary society. The demise of traditional preaching is discussed as problematic. A cursory investigation is launched into the impact of the developing digital culture on communication and homiletics. The attention then shifts to the communication model as developed by Heath and Heath, in their book, “Made to Stick.” This model is subsequently adapted for the purposes of sermon preparatin and a digital-culture homiletic praxis.